Assessment of microbial plankton diversity as an ecological indicator in the NW Mediterranean coast. (November 2020) - Ferrera, Isabel; Reñé, Albert; Funosas, David; Camp, Jordi; Massana, Ramon; Gasol, Josep M.; Garcés, Esther
Abstract: High-throughput sequencing of microbial assemblages has been proposed as an alternative methodology to the traditional ones used in marine monitoring and environmental assessment. Here, we evaluated pico- and nanoplankton diversity as ecological indicators in NW Mediterranean coastal waters by comparing their diversity in samples subjected to varying degrees of continental pressures. Using metabarcoding of the 16S and 18S rRNA genes, we explored whether alphadiversity indices, abundance of Operational Taxonomic Units and taxonomic groups (and their ratios) provide information on the ecological quality of coastal waters. Our results revealed that only eukaryotic diversity metrics and a limited number of prokaryotic and eukaryotic taxa displayed potential in assessing continental influences in our surveyed area, resulting thus in a restrained potential of microbial plankton diversity as an ecological indicator. Therefore, incorporating microbial plankton diversity in environmental assessment could not always result in a significant improvement of current marine monitoring strategies. Graphical abstract: Unlabelled Image Highlights: We evaluated pico- and nanoplankton diversity as ecological indicators in coastal waters using metabarcoding of rRNA genes Studied samples were subjected to varying degrees of continental pressures Diversity metrics from microbial eukaryotes displayed more suitability as indicators than those of prokaryotes Few microbial planktonic taxa (both from prokaryotes and eukaryotes) showed potential as indicators Implementing ecological indicators from microbial plankton communities is challenging due to their complexity and dynamics